2008
DOI: 10.1103/physreve.78.046609
|View full text |Cite
|
Sign up to set email alerts
|

Electromagnetic transparency by coated spheres with radial anisotropy

Abstract: We establish an account of electromagnetic scattering by coated spheres with radial dielectric and magnetic anisotropy. Within full-wave scattering theory, we show that the total scattering cross section Qs is strongly dependent on both the dielectric anisotropy and magnetic anisotropy. As a consequence, by a suitable adjustment of the radius ratio, one may make the anisotropic coated particle nearly transparent or invisible. In the quasistatic case, we take one step forward to derive the effective permittivit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
51
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 74 publications
(53 citation statements)
references
References 43 publications
2
51
0
Order By: Relevance
“…In this situation, the effective scattering width of the cylinder is determined by m = 0 and m = 1 terms [26,27]. Note that for incident TM wave, the effective permittivity and permeability are still isotropic for radial anisotropy [28,29].…”
Section: Formalismmentioning
confidence: 99%
“…In this situation, the effective scattering width of the cylinder is determined by m = 0 and m = 1 terms [26,27]. Note that for incident TM wave, the effective permittivity and permeability are still isotropic for radial anisotropy [28,29].…”
Section: Formalismmentioning
confidence: 99%
“…Based on scattering theory [28,29], the scattered wave can be regarded as a superposition of TE and TM waves, and we can obtain the scattering coefficients in free space, i.e. A TM n and A TE n [13],…”
Section: Theoretical Modelmentioning
confidence: 99%
“…More recently, it was found that spherical anisotropy plays an important role in achieving the enhancement of nonlinear susceptibilities for second-and third-harmonic generation and controlling resonant frequencies [26]. Furthermore, the suitable adjustment of spherical anisotropy of the coreshell particle can also result in a tunable electromagnetic cloaking [13]. In addition, the near-field and far-field optical properties of coated particles with metallic core and spherically anisotropic shell [2] or with metallic shell and spherically anisotropic core [27] have already been investigated, which are only valid under the electrostatic condition, i.e.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Papers [41] and [40] consider using cylindrical RA shells for cloaking purposes, whereas [42,43] focus on the peculiarities of light scattering from plasmonic RA cylinders. For the analysis, occurrence and applications of 3D radially-anisotropic spheres, see [44,45] and the references therein. Mie resonances of anisotropic spheres have also been studied in [46], but the anisotropy is given with respect to rectangular coordinates.…”
Section: Introductionmentioning
confidence: 99%